The chemokine receptor CXCR4 regulates satellite cell activation, early expansion, and self-renewal, in response to skeletal muscle injury - Shams, Ahmed S.; Arpke, Robert W.; Gearhart, Micah D.; Weiblen, Johannes; Mai, Ben; Oyler, David; Bosnakovski, Darko; Mahmoud, Omayma M.; Hassan, Gamal M.; Kyba, Michael (Frontiers in Cell and Developmental Biology, 2022)
Acute skeletal muscle injury is followed by satellite cell activation, proliferation, and differentiation to replace damaged fibers with newly regenerated muscle fibers, processes that involve satellite cell interactions with various niche signals. Here we show that satellite cell specific deletion of the chemokine receptor CXCR4, followed by suppression of recombination escapers, leads to defects in regeneration and satellite cell pool repopulation in both the transplantation and in situ injury contexts. Mechanistically, we show that endothelial cells and FAPs express the gene for the ligand, SDF1α, and that CXCR4 is principally required for proper activation and for transit through the first cell division, and to a lesser extent the later cell divisions. In the absence of CXCR4, gene expression in quiescent satellite cells is not severely disrupted, but in activated satellite cells a subset of genes normally induced by activation fail to upregulate normally. These data demonstrate that CXCR4 signaling is essential to normal early activation, proliferation, and self-renewal of satellite cells.